2018
DOI: 10.5194/bg-15-1775-2018
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide emissions from the flat bottom and shallow Nam Theun 2 Reservoir: drawdown area as a neglected pathway to the atmosphere

Abstract: Abstract. Freshwater reservoirs are a significant source of CO2 to the atmosphere. CO2 is known to be emitted at the reservoir surface by diffusion at the air–water interface and downstream of dams or powerhouses by degassing and along the river course. In this study, we quantified total CO2 emissions from the Nam Theun 2 Reservoir (Lao PDR) in the Mekong River watershed. The study started in May 2009, less than a year after flooding and just a few months after the maximum level was first reached and lasted un… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 62 publications
(143 reference statements)
3
12
0
Order By: Relevance
“…The drawdown area thus accounted for < 20% of the total reservoir area but contributed to > 80% of total reservoir CO 2 emissions upstream the dam. Our results are in line with a recent study conducted in a reservoir in Southeast Asia, which found that drawdown areas accounted for 50-75% of total annual reservoir CO 2 emission (Deshmukh et al 2018). Our findings indicate that drawdown areas are CO 2 emission hotspots in CDU reservoir, not only due to high emission rates in relation to reservoir water surface, but also because exposed sediments cover a large fraction of the total reservoir area over long periods of the year (Fig.…”
Section: Relative Contribution Of Drawdown Areas To Total Reservoir Csupporting
confidence: 92%
See 3 more Smart Citations
“…The drawdown area thus accounted for < 20% of the total reservoir area but contributed to > 80% of total reservoir CO 2 emissions upstream the dam. Our results are in line with a recent study conducted in a reservoir in Southeast Asia, which found that drawdown areas accounted for 50-75% of total annual reservoir CO 2 emission (Deshmukh et al 2018). Our findings indicate that drawdown areas are CO 2 emission hotspots in CDU reservoir, not only due to high emission rates in relation to reservoir water surface, but also because exposed sediments cover a large fraction of the total reservoir area over long periods of the year (Fig.…”
Section: Relative Contribution Of Drawdown Areas To Total Reservoir Csupporting
confidence: 92%
“…An important factor supporting enhanced CO 2 emission rates from exposed sediments is the increased microbial metabolism (e.g., enhanced enzyme activity of phenol oxidases and hydrolases) as sediment dries out (Hyojin et al 2016;Weise et al 2016). The importance of exposed sediments to reservoir carbon processing is clearly illustrated by a study in a Southeast Asian reservoir, which demonstrates that drawdown areas may contribute up to 75% of total annual CO 2 emissions (Deshmukh et al 2018). Globally, dry exposed sediments are estimated to emit ~ 200 Tg of carbon as CO 2 , which is equivalent to ~ 10% of global CO 2 emissions from inland waters (Marcé et al 2019).…”
Section: Aquatic Sciencesmentioning
confidence: 99%
See 2 more Smart Citations
“…) and thus some labile sedimentary carbon stores were likely converted to CO 2 via aerobic pathways and evaded to the atmosphere, resulting in a net loss of labile carbon between C1 and C2. Even relatively small drawdown areas and drying of sediments have been shown to significantly enhance carbon losses and retard subsequent methanogensis upon reflooding (Chimner and Cooper ; Knorr et al ; Deshmukh et al ), with significant alteration to the microbial community following drought events (Rees et al ). After the initial suppression of methane production during water table drawn down, reflooding events eventually cause methane concentrations to increase with the timing of recovery ranging from a matter of days to months (Boon et al ; Knorr et al ; Tyler et al ).…”
Section: Discussionmentioning
confidence: 99%